COmmunity-based Rehabilitation after Knee Arthroplasty (CORKA): statistical analysis plan for a randomised controlled trial - Vadher, K; Knight, R; Barker, K; Dutton, S (BioMed Central, 2018)
Background About 15% of patients fail to achieve a satisfactory clinical outcome following knee replacement, which may indicate the existing model of rehabilitation after surgery is possibly not the most efficacious. The COmmunity-based Rehabilitation after Knee Arthroplasty (CORKA) trial evaluates the effects of a new multi-component community-based rehabilitation programme following knee replacement compared with usual care. Methods/design The CORKA trial is a multi-centre, single-blind, two-arm randomised controlled trial. The primary outcome is the Late Life Function and Disability Instrument (LLFDI) overall function score measured at 12 months post-randomisation which will be analysed using a linear mixed effects model. Secondary outcomes are measured at 6 and 12 months post-randomisation and include the LLFDI frequency and limitation total dimension scores, the Oxford Knee Score, the Knee injury and Osteoarthritis Outcome Score quality of life subscale, the Physical Activity Scale for the Elderly, the EuroQol EQ-5D-5L, and several measurements of physical function. Full details of the planned analysis approaches for the primary and secondary outcomes are described here, as are the descriptive statistics which will be reported. This is an update to the CORKA protocol which has already been published in this journal. Discussion This paper provides details of the planned statistical analyses for this trial and will reduce the risks of outcome reporting bias and data-driven results. Trial registration ISRCTN registry, 13517704. Registered on 12 February 2015. Funding/sponsor The trial is funded by the National Institute for Health Research Health Technology Assessment programme under its commissioned research programme (HTA 12/196/08). The trial sponsor is the University of Oxford.